2019
DOI: 10.1038/s41598-019-49228-4
|View full text |Cite
|
Sign up to set email alerts
|

Composition and physico-chemical properties of bottom sediments in the southern part of the Bratsk Reservoir (Russia)

Abstract: The paper presents the results of studies of bottom sediments taken from the southern part of the Bratsk Reservoir. The following analyses have been conducted: trace element analysis, particle-size analysis as well as chemical analysis of water, hydrochloric acid and alkaline extracts for 18 samples of the bottom sediments. The granulometric analysis has identified the predominance of fine silt and silty-clayed sediments. The data on the content of trace elements in the bottom sediments of the Bratsk Reservoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…The sediment particle size has a great influence on the distribution of natural and anthropogenic elements, as organic matter, nutrients and metals, showing usually high affinity to fine particles (<0.063 nm) [26,27,64]. These compounds may be released from the sediments to the bottom phase of the water column under specific limnological conditions.…”
Section: Sediments Seasonal and Spatial Dynamics 331 Granulometricmentioning
confidence: 99%
“…The sediment particle size has a great influence on the distribution of natural and anthropogenic elements, as organic matter, nutrients and metals, showing usually high affinity to fine particles (<0.063 nm) [26,27,64]. These compounds may be released from the sediments to the bottom phase of the water column under specific limnological conditions.…”
Section: Sediments Seasonal and Spatial Dynamics 331 Granulometricmentioning
confidence: 99%
“…1 c). The composition of the Bratsk bottom sediments on the site from Svirsk to Unga Bay revealed that the total content of carbonates, with a predominance of CaCO 3 and MgCO 3 , averaged to 24% 19 . With time, the sediment-forming terrigenous material underwent leaching that resulted in the increase of Ca 2+ , Mg 2+ , HCO 3 − and SO 4 2− concentrations in the Bratsk reservoir pore water.…”
Section: Discussionmentioning
confidence: 99%
“…3 , 4 ) indicate that the bottom sediments undergo reduced diagenetic transformations whose intensity depends on the amount of organic matter 54 . In the Bratsk Reservoir bottom sediments, on the site from Svirsk to Unga Bay, the organic carbon content is on average, 5.60%, with its highest concentration in the bottom sediments of the bays (to 17.7%) 19 . It should be noted that large amounts of organic materials were brought during the reservoir filling when 166 thousand hectares of agricultural land and 135.2 thousand hectares of forest were flooded 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, water ow slowdown and changes in sedimentation conditions after the river ow reservoirs, the Bratsk, the second of the cascade, whose lling was completed in 1967, is considered the most technogenically-stressed. Despite there is great amount of information concerning the elemental composition of water [16][17][18], bottom sediments [19,20] and biota [21] of the Bratsk reservoir, yet, the pore water chemistry remains an insu ciently studied geochemical sector. The pore water studies, done in 1980ies, the initial period of the reservoir operation [22], included only the determination of main cations (Na + , K + , Ca 2 + , Mg 2+ ) and biogenic components (NO 3 -, SiO 2 -, PO 4 3-) in the pore solution.…”
Section: Introductionmentioning
confidence: 99%